2015
DOI: 10.1542/peds.2014-1345
|View full text |Cite
|
Sign up to set email alerts
|

Independent Living and Romantic Relations Among Young Adults Born Preterm

Abstract: BACKGROUND: Young adults born preterm at very low birth weight start families later. Whether less severe immaturity affects adult social outcomes is poorly known. METHODS: The study “Preterm birth and early life programming of adult health and disease” (ESTER, 2009–2011) identified adults born early preterm (<34 weeks’ gestation, N = 149), late preterm (≥34 to <37 weeks’ gestation, N = 248), and at term (≥37 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
3
16
0
2
Order By: Relevance
“…Our findings suggest that higher rates of psychiatric problems and antidepressant medication could be partly explained by VP/VLBW adults' higher risk of being without a romantic partner rather than due to increased depression symptomatology. This is consistent with repeated findings that VP/VLBW have higher scores for socially withdrawn personality traits (Eryigit Madzwamuse et al, 2015;Waxman, Van Lieshout, Saigal, Boyle, & Schmidt, 2013) and romantic relationship problems (M€ annist€ o et al, 2015;Saigal et al, 2016). In accordance with recent findings (Van Lieshout et al, 2015), our supplementary data suggest an increased prevalence of social phobia in VP/VLBW adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings suggest that higher rates of psychiatric problems and antidepressant medication could be partly explained by VP/VLBW adults' higher risk of being without a romantic partner rather than due to increased depression symptomatology. This is consistent with repeated findings that VP/VLBW have higher scores for socially withdrawn personality traits (Eryigit Madzwamuse et al, 2015;Waxman, Van Lieshout, Saigal, Boyle, & Schmidt, 2013) and romantic relationship problems (M€ annist€ o et al, 2015;Saigal et al, 2016). In accordance with recent findings (Van Lieshout et al, 2015), our supplementary data suggest an increased prevalence of social phobia in VP/VLBW adults.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have found that VP/VLBW young adults often have poor social support and are less likely to engage in romantic relationships than termborn adults (D'Onofrio et al, 2013;Darlow, Horwood, Pere-Bracken, & Woodward, 2013;M€ annist€ o et al, 2015). A supportive partner relationship can provide protection against the development of psychiatric problems (La Greca & Harrison, 2005;Ozbay, Fitterling, Charney, & Southwick, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We have been able to take in account a wide range of confounding factors, although the risk of residual confounding still remains a possibility. As previously reported (37), those born preterm live at their parents' home longer, which may improve their dietary choices. This was adjusted for in the analyses.…”
Section: Discussionsupporting
confidence: 55%
“…Several international studies on the young adult outcomes of very premature infants have been published in the last decade from Canada, [1][2][3][4][5] the United States, 6,7 England, 8 Sweden, 9 Norway, 10 the Netherlands, 11 Denmark, 12 Finland, 13 and Australia. 14 These reports reveal that these individuals have poorer educational 6,[8][9][10][11] and employment outcomes, 6,11 fewer leave the parental home, 13 and more experience delays in the onset of sexual activity, 6,8,11,13,15 marriage or cohabitation, 7,13,15 and reproduction. [16][17][18] In addition, a higher prevalence of chronic physical 4,7,14 and mental health issues 5,[19][20][21][22] have been noted, although risk-taking behaviors appear to be less common.…”
mentioning
confidence: 99%